2023
DOI: 10.1029/2022gl101226
|View full text |Cite
|
Sign up to set email alerts
|

Opposite Impacts of Interannual and Decadal Pacific Variability in the Extratropics

Abstract: The El Niño Southern Oscillation (ENSO) is the dominant mode of interannual climate variability in the Pacific, and its global impacts have been extensively studied (e.g., Taschetto et al., 2020;Yeh et al., 2018). In particular, El Niño, the positive ENSO phase, tends to promote a negative North Atlantic Oscillation (NAO) and cold winters in northern Europe (Brönnimann, 2007). This connection occurs through both tropospheric and stratospheric pathways (Domeisen et al., 2019;Hardiman et al., 2019). In the tropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 95 publications
0
3
0
Order By: Relevance
“…Here evidence of such feedback was shown to be particularly strong under the largest SAI scenario, that is, when the higher stratospheric aerosol levels drive larger chemical ozone losses that can then modulate the polar vortex dynamics. Finally, though not examined in detail in this study, changes in stratospheric water vapor have also been shown to drive changes in the high latitude circulation (Maycock et al, 2013;Seabrook et al, 2023), as well as enhance catalytic ozone loss (Tilmes et al, 2021), but uncertainties remain as to the details of such responses. Since SAI-induced lower stratospheric warming also drives significant increases in stratospheric water vapor, this process constitutes an additional source of uncertainty to the overall SAI impacts in the high latitudes.…”
Section: Summary and Discussionmentioning
confidence: 91%
“…Here evidence of such feedback was shown to be particularly strong under the largest SAI scenario, that is, when the higher stratospheric aerosol levels drive larger chemical ozone losses that can then modulate the polar vortex dynamics. Finally, though not examined in detail in this study, changes in stratospheric water vapor have also been shown to drive changes in the high latitude circulation (Maycock et al, 2013;Seabrook et al, 2023), as well as enhance catalytic ozone loss (Tilmes et al, 2021), but uncertainties remain as to the details of such responses. Since SAI-induced lower stratospheric warming also drives significant increases in stratospheric water vapor, this process constitutes an additional source of uncertainty to the overall SAI impacts in the high latitudes.…”
Section: Summary and Discussionmentioning
confidence: 91%
“…We expect to see some agreement because the ENSO SST pattern projects heavily onto the PDO SST pattern (the key difference being the relative strength of the North and tropical Pacific anomalies). On the other hand, there is evidence that the interaction between Pacific SST variability and the extratropics can be dependent on time scale (Seabrook et al, 2023). If the decadal variability discussed in Section 4.1 is an aliasing of the interannual ENSO variability, similar changes to the MJO response between El Niño and La Niña as between period one and two might be expected.…”
Section: Interannual Changes Associated With Ensomentioning
confidence: 98%
“…We expect to see some agreement because the ENSO SST pattern projects heavily onto the PDO SST pattern (the key difference being the relative strength of the North and tropical Pacific anomalies). On the other hand, there is evidence that the interaction between Pacific SST variability and the extratropics can be dependent on time scale (Seabrook et al., 2023). If the decadal variability discussed in Section 4.1 is an aliasing of the interannual ENSO variability, similar changes to the MJO response between El Niño and La Niña as between period one and two might be expected.…”
Section: Changes In the Upper Tropospheric Response To The Mjomentioning
confidence: 99%
“…However, there is little understanding of the variability of MJO teleconnections on decadal time scales. Furthermore, the extratropics have been shown to respond differently to remote forcing on interannual and decadal time scales (Seabrook et al., 2023).…”
Section: Introductionmentioning
confidence: 99%